Effect of fermentation on immunological properties of allergens from black carp (Mylopharyngodon piceus) sausages. (25th April 2020) - Zhu, Yidan; Gao, Ling; Xie, Guojin; Yang, Fang; Gao, Pei; Yu, Dawei; Yu, Peipei; Jiang, Qixing; Xu, Yanshun; Xia, Wenshui
Summary: The increased fish consumption correlates with increased hypersensitive reactions, which can reduce consumer's living quality. Therefore, the reduction by fish allergens by new technologies is important. The aim of this study was to evaluate the effect of different starter cultures, fermentation process and additives used in fermentation on immunological properties of fish allergens. The results showed that fermentation with Lactobacillus plantarum reduced the IgG‐ and IgE‐binding capacity (39.71 ± 6.18% and 76.12 ± 4.73%, respectively) the most, compared with Staphylococcus xylosus and Saccharomyces cerevisiae, and the reduction rate was the highest atthe end of fermentation and an incubation concentration at 1.5% (v/w). A change in the NaCl content affected immunological properties of fish allergenic proteins during fermentation, while a change in glucose had less impact. In conclusion, fermentation can be used to reduce the immunological propertis of fish allergens due to structural changes in proteins caused by enzymatic hydrolysis, acidity or ion strength. Abstract : Different starter culturers, fermentation time, concentration of Lactobacillius plantarum and additives used in fermentation have different effect on the IgE‐binding capacity of allergens from black carp.